Predation risks of signalling and searching: bats prefer moving katydids. (29th April 2020) - Geipel, Inga; Kernan, Ciara E.; Litterer, Amber S.; Carter, Gerald G.; Page, Rachel A.; ter Hofstede, Hannah M.
Abstract : Males signalling their attractiveness to females are at risk from predators that exploit mating signals to detect and locate prey. Signalling, however, is not the only risky activity in sexual interactions: mate searching can incur risk as well. Male Neotropical pseudophylline katydids produce both acoustic and vibrational signals (tremulations). Females reply to male signals with tremulations of their own, and both sexes walk to find one another. We asked if movement increases predation risk, and whether tremulation or walking was more attractive to predators. We offered the Neotropical gleaning bat Micronycteris microtis a series of two-choice tests, presenting the bats with katydid models that were motionless or moved in a way to mimic either tremulating or walking. We found that prey movements do put prey at risk. Although M. microtis can detect motionless prey on leaves, they preferred moving prey. Our study shows that movement can put searching or signalling prey in danger, potentially explaining why silent female katydids are frequently consumed by gleaning bats.